TRUFU: Therapeutic radiographer undertaking follow up for prostate cancer patients. Issue 4 (November 2018) - Hetherington, S.M.; Gilleece, T.; Shepherd, P.; Crowther, K.; O'Sullivan, J.; Jain, S.; Mitchell, D.; Shum, L.; Turner, P.
Abstract: Introduction: A study was proposed to examine the impact to patients and the Oncology review team, of extending the role of the Therapeutic Radiographer to undertake follow up review of prostate cancer patients who have completed a radical course of external beam radiotherapy treatment. Method: A total of 30 patients attending for routine radiotherapy follow up were included in an observational study. Patients were assigned for review with a Doctor or a Therapeutic Radiographer using 1:1 randomisation and a number of time points were recorded and analysed. Results: Of the 44 patients screened, 30 patients were recruited. Average time from scheduled appointment time to departure from clinic was 36 min for both the doctor and Therapeutic Radiographer. The average length of Consultation was 19 min for the Therapeutic Radiographer and 10 min for the Doctor. Average length of wait for patients from scheduled appointment time to being taken for review was 17 min for the Therapeutic Radiographer and 25 min for the Doctor. Of the patients who completed questionnaires, 23/28 had no preference of reviewer, 2/28 declared a preference to be seen by a doctor, whilst 3/28 stated a preference for review with a Therapeutic Radiographer. Conclusion: The results of the study are encouraging and should be further investigated in an attempt of developing what would be a very rewarding aspect of the Therapeutic Radiographers role. Highlights: Therapeutic Radiographer able to take patients for review quicker than doctor. Therapeutic Radiographer able to offer patients longer consultation. More study participants stated preference for review with Therapeutic Radiographer.